Material Management: A Sustainable Way to Reduce the Wastage - Balar, Karm P.; Shah, Rushabh A.; Shah, Jayesh A. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
In today’s world construction work are going at unexpected speed in all area like building, bridge, high-rise and so on. As we know there are two side of coin same way there are some disadvantage of this speedy construction which leads towards a wastage, like Material, Money, Time, and so on. One of the most important part of wastage is due to Improper Material Management. If we not prepare good management technic of material management than it convert in to wastage. It shall be very hard to manage wastage rather than managing the material. So if we want to manage the waste we need to manage the material in Proper Way. For that first of all we need to find out the importance of Phases of Material Management and Crucial Factors which affects the material management.